Village Financial Management Training Equipped with SisKeuDes Supporting Application Design in Parongpong District, West Bandung Regency - Riauli Susilawaty Hutapea; Arwan Gunawan; Muhammad Umar Mai; Sudradjat; Sugih Sutrisno Putra; Tjetjep Djuwarsa (Jurnal Pengabdian Masyarakat Bestari, 2022)
The Bandung State Polytechnic (Polban) Accounting Department intends to participate in providing solutions to problems faced by villages in Parongpong District through the Community Service (PkM) program. The solution offered is to increase the knowledge and competence of village government officials regarding financial governance through training on the Budget Cycle and Accounting Cycle for DD and ADD administration, followed by a mentoring program in using supporting applications for the Village Financial System. This activity is also intended as a media for students to apply their knowledge directly in the community in relevant fields, a form of link and match between AMP Study Program and users, namely local government, and a form of self-actualization of students in society. The results of the implementation of the PkM program activities that have been carried out include: Training related to the provision of material on the Budget Cycle and Accounting Cycle as well as Assistance regarding the Practice of Using Village Financial System Support Applications (SisKeuDes), as well as ways to understand and overcome the Inspector General's findings.